1989
DOI: 10.1152/ajpregu.1989.256.1.r264
|View full text |Cite
|
Sign up to set email alerts
|

Brain stem mechanisms and the inhibition of angiotensin-induced drinking

Abstract: The present studies examine the effect of lesions of the ventrolateral region of the lateral parabrachial nucleus (VLLPBN) and of the area postrema and medial region of the nucleus of the solitary tract (AP/mNTS) on water intake induced by intracerebroventricular administration of angiotensin II (ANG II) and of the cholinergic receptor agonist, carbachol. Water intake was measured in rats with bilateral electrolytic lesions of the VLLPBN or thermocautery ablation of the AP/mNTS after intracerebroventricular de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
31
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…Initial studies on the role of the LPBN in the control of fluid and electrolyte balance were directed at investigating hindbrain control of water intake. Results from these experiments showed that electrolytic or neurotoxic lesions of the LPBN increased thirst induced by manipulations that are related to the depletion of extracellular fluid but not to the reduction of intracellular volume (44,105,106). Also the inactivation of LPBN neurons with bilateral injections of lidocaine or by nonselective antagonism of serotonin receptors by injecting methysergide into the LPBN increased ANG II-induced water intake (94).…”
mentioning
confidence: 99%
“…Initial studies on the role of the LPBN in the control of fluid and electrolyte balance were directed at investigating hindbrain control of water intake. Results from these experiments showed that electrolytic or neurotoxic lesions of the LPBN increased thirst induced by manipulations that are related to the depletion of extracellular fluid but not to the reduction of intracellular volume (44,105,106). Also the inactivation of LPBN neurons with bilateral injections of lidocaine or by nonselective antagonism of serotonin receptors by injecting methysergide into the LPBN increased ANG II-induced water intake (94).…”
mentioning
confidence: 99%
“…Dorsal to the bc, the pPB area centered in the central lateral (pPBcl) and the external lateral (pPBel) subnuclei are involved in numerous autonomic processes (Mraovitch et al, 1982;Cechetto and Calaresu, 1983;Darlington and Ward, 1985a,b;Lumb and Morrison, 1987;Ward, 1988Ward, , 1989Ohman and Johnson, 1989;Herbert et al, 1990;Chamberlin and Saper, 1992).…”
mentioning
confidence: 99%
“…The lateral and external parts of this area respond to noxious stimuli (Bernard and Besson, 1990;Bernard et al, 1994;Bester et al, 1995c). This region is also involved in different autonomic regulatory processes (Bertrand and Hugelin, 1971;Mraovitch et al, 1982;Cechetto and Calaresu, 1983;Darlington and Ward, 1985a,b;Lumb and Morrison, 1987;Ward, 1988Ward, , 1989Ohman and Johnson, 1989;Herbert et al, 1990;Jhamandas et al, 1991;Chamberlin and Saper, 1992) and aversive behaviour (Berntson, 1973;Berntson et al, 1988;Depoortere et al, 1990a,b;Bucherelli and Tassoni, 1992;Agü ero et al, 1993;Bechara et al, 1993). The lateral and external parts of the PB area are also a major relay, transmitting nociceptive information from the lamina I neurones to either the centralis nucleus (Ce) of the amygdala or the ventromedial (VMH) nucleus of the hypothalamus (Wiberg and Blomqvist, 1984;Cechetto et al, 1985;Hylden et al, 1985Hylden et al, , 1986McMahon and Wall, 1985;Swett et al, 1985;Light et al, 1987Light et al, , 1993Tabata, 1989, 1990;Lima and Coimbra, 1989a,b;Bernard and Besson, 1990;Yamada and Kitamura, 1992;Kitamura et al, 1993;Bernard et al, 1994Bernard et al, , 1995Slugg and Light, 1994;Bester et a...…”
mentioning
confidence: 99%